Limited legal status for refugees from Syria in Lebanon - Aranki, D; Kalis, O (Refugee Studies Centre, University of Oxford, 2014)
Having limited legal status has direct negative consequences for Syrian refugees’ access to protection and assistance during their stay in Lebanon. Limited legal status also increases the risks of abuse and exploitation.